Manajemen Humas dan Pemasaran Pendidikan - Aprianto, Iwan; Mahdayeni, Mahdayeni; Riyadi, Sugeng; Wahyuni , Sri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The education sector today faces increasingly complex and dynamic challenges driven by rapid global changes, digital technological advancements, and rising public expectations for high-quality education. Intense competition among educational institutions requires innovative and adaptive management strategies to build a positive image, strengthen public trust, and attract prospective students. In this context, public relations (PR) management and educational marketing play essential and mutually supportive roles in maintaining institutional reputation and sustainability. PR functions as a strategic connector between institutions and stakeholders through two-way communication, information transparency, media management, and crisis communication, all of which contribute to building a positive public image. Meanwhile, educational marketing focuses on identifying needs, creating value, and promoting institutional strengths such as academic achievements, facilities, and alumni success through both conventional and digital platforms. The integration of PR and marketing enables consistent, ethical, and data-driven communication strategies that translate public trust into increased student enrollment and competitive advantage. The effectiveness of these strategies is strongly influenced by external factors such as technological development and globalization, as well as internal factors including the competence of human resources. Therefore, the synergy between PR and educational marketing becomes a key strategy in improving institutional quality, reputation, competitiveness, and long-term sustainability in the rapidly evolving global education landscape.